Chapter Identifying, Classifying and Searching Graphic Symbols in the NOTAE System - BOCCUZZI, Maria (Springer Nature, 2020)
The use of graphic symbols in documentary records from the 5th to the 9th century has so far received scant attention. What we mean by graphic symbols are graphic signs (including alphabetical ones) drawn as a visual unit in a written text and representing something other or something more than a word of that text. The Project NOTAE represents the first attempt to investigate these graphic entities as a historical phenomenon from Late Antiquity to early medieval Europe in any written sources containing texts generated for pragmatic purposes (contracts, petitions, official and private letters, lists etc.). Identifying and classifying graphic symbols on such documents is a task that requires experience and knowledge of the field, but software applications may come in help by learning to recognize symbols from previously annotated documents and suggesting experts potential symbols and likely classification in newly acquired documents to be validated, thus easing the task. This contribution introduces the NOTAE system that, in addition to the aforementioned task, provides non expert users with tools to explore the documents annotated by experts.